2019
DOI: 10.1519/jsc.0000000000003002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sports Compression Socks on Performance, Physiological, and Hematological Alterations After Long-Haul Air Travel in Elite Female Volleyballers

Abstract: The purpose of this investigation was to assess the merit of sports compression socks in minimizing travel-induced performance, physiological, and hematological alterations in elite female volleyball athletes. Twelve elite female volleyballers (age, 25 ± 2 y) travelled from Canberra (Australia) to Manila (Philippines), and were assigned to one of two conditions; compression socks (COMP, n = 6) worn during travel, or a passive control (CON, n = 6). Dependent measures included counter-movement jump (CMJ) perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Nonetheless, there were a number of studies reporting beneficial effects on jump [3,27,31,39,69,73,85,86,91,103,[117][118][119][120][121][122], time trial/race [5,17,72,[123][124][125][126], sprint [22,73,[126][127][128][129], and agility [73,130,131] performance. A similar pattern was identified with time to exhaustion/ fatigue, as compression is reported to improve [8,132] or have no effect [9,12,36,133,134] on time to fatigue.…”
Section: Performance and Muscle Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nonetheless, there were a number of studies reporting beneficial effects on jump [3,27,31,39,69,73,85,86,91,103,[117][118][119][120][121][122], time trial/race [5,17,72,[123][124][125][126], sprint [22,73,[126][127][128][129], and agility [73,130,131] performance. A similar pattern was identified with time to exhaustion/ fatigue, as compression is reported to improve [8,132] or have no effect [9,12,36,133,134] on time to fatigue.…”
Section: Performance and Muscle Functionmentioning
confidence: 99%
“…A small number of studies investigated other blood markers including glucose [64,89,93,119,120], blood pH [15,22,50,87,164,171], oxygen saturation of haemoglobin [12,15,50,93,167], and partial pressure of oxygen [12,15,50], with no effect of compression reported, with the exception of a positive effect in one study measuring oxygen saturation of haemoglobin [167]. For markers of coagulation and fibrinolysis two studies reported no effect [122,169], and one study [170] reported a positive effect on thrombin-antithrombin complex and plasminogen activator inhibitor with compression. However, one study [172] reported a negative effect of compression on d-dimer.…”
Section: Blood and Salivary Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is still unknown whether hypohydration per se accelerates declines in physical performance or imposes additional fatigue development following transmeridian air travel, since rapidly crossing multiple time zones is known to impair physical performance. Jet lag side effects and subsequent performance outcome parameters that have been assessed are diverse, including jump performance [48][49][50], sprint performance [48,49], isometric adductor strength [47], and handgrip strength [51,52], all presented in Table 2. Performance decrements were predominantly observed throughout the explosive movement of the lower limbs (e.g., countermovement jump decreases immediately upon arrival by 7-10%, and a similar pattern was observed in sprint performance), but not during isometric contractions of the lower or upper limbs.…”
Section: Hypohydration Jet Lag and Performancementioning
confidence: 99%